2021
DOI: 10.13048/jkm.21030
|View full text |Cite
|
Sign up to set email alerts
|

Review of Latest Traditional Chinese Medicine Clinical Studies on Pediatric Tic Disorder with Tuina Treatment

Abstract: Objectives: The purpose of this review is to investigate the latest traditional Chinese medicine clinical studies on pediatric tic disorder with Tuina treatment and propose the directions of future studies and clinical applications. Methods: To obtain data from CNKI, set the field by ‘中醫學’, ‘中藥’, ‘中西醫結合’ and used keywords ‘抽动障碍’, ‘抽動 穢語綜合’, ‘小兒抽动’, ‘兒童抽动’ and ‘推拿’, ‘導引’, ‘按摩’, ‘Tuina’, ‘massage’ in cross combination way. Results: 12 clinical studies were selected. These studies were analyzed by author & ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…Massage therapy for Tic disorders has been used to some extent in China and South Korea. Meta-analytical studies have shown that compared with conventional therapies, Massage therapy possesses unique advantages such as low pain, significant clinical efficacy, and reduced likelihood of recurrence [10,11]. The results provide clinical evidence for the use of traditional Chinese medicine and massage in the treatment of Tic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Massage therapy for Tic disorders has been used to some extent in China and South Korea. Meta-analytical studies have shown that compared with conventional therapies, Massage therapy possesses unique advantages such as low pain, significant clinical efficacy, and reduced likelihood of recurrence [10,11]. The results provide clinical evidence for the use of traditional Chinese medicine and massage in the treatment of Tic disorders.…”
Section: Discussionmentioning
confidence: 99%